2012
DOI: 10.1021/ic300932a
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Nitro Complex with an Anionic [HB(3,5-Me2Pz)3] Ligand: A Synthetic Model for the Copper Nitrite Reductase Active Site

Abstract: The new copper(I) nitro complex [(Ph(3)P)(2)N][Cu(HB(3,5-Me(2)Pz)(3))(NO(2))] (2), containing the anionic hydrotris(3,5-dimethylpyrazolyl)borate ligand, was synthesized, and its structural features were probed using X-ray crystallography. Complex 2 was found to cocrystallize with a water molecule, and X-ray crystallographic analysis showed that the resulting molecule had the structure [(Ph(3)P)(2)N][Cu(HB(3,5-Me(2)Pz)(3))(NO(2))]·H(2)O (3), containing a water hydrogen bonded to an oxygen of the nitrite moiety.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 58 publications
0
45
1
Order By: Relevance
“…[30] Comparing to other (L)Cu II NO 2 complexes in the literature, our Cu II/I redox potential is much higher than the values for L 1 and L 2 complexes described in the introduction (E 1/2 = -0.027 V and -0.375 V vs. SCE with L 1 and L 2 , respectively) which makes sense because these ligands are stronger donors than Ttz tBu,Me . [26][27][28] Notice that the reduction potential we observed for 2 at 0.18 V is much higher than the value we previously reported for E pc of -1.45 V (vs. a non-aqueous Ag/Ag(ClO 4 ), or -1.15 V vs. SCE reference electrode in CH 2 Cl 2 ). [8,65] We conclude that this reduction potential was in error due to the high resistivity of the solution (CH 2 Cl 2 ) which was previously not accounted for using the Ohmic drop (iR) method.…”
Section: Electrochemistrycontrasting
confidence: 70%
See 2 more Smart Citations
“…[30] Comparing to other (L)Cu II NO 2 complexes in the literature, our Cu II/I redox potential is much higher than the values for L 1 and L 2 complexes described in the introduction (E 1/2 = -0.027 V and -0.375 V vs. SCE with L 1 and L 2 , respectively) which makes sense because these ligands are stronger donors than Ttz tBu,Me . [26][27][28] Notice that the reduction potential we observed for 2 at 0.18 V is much higher than the value we previously reported for E pc of -1.45 V (vs. a non-aqueous Ag/Ag(ClO 4 ), or -1.15 V vs. SCE reference electrode in CH 2 Cl 2 ). [8,65] We conclude that this reduction potential was in error due to the high resistivity of the solution (CH 2 Cl 2 ) which was previously not accounted for using the Ohmic drop (iR) method.…”
Section: Electrochemistrycontrasting
confidence: 70%
“…We postulated that the reduction potential from Cu II to Cu I of (Ttz tBu,Me )Cu II NO 2 (2) should similarly be sensitive to the addition of acid. The cyclic voltammogram of (Ttz tBu,Me )Cu(II)NO 2 (2) with varied amounts of HBF 4 and the resulting electrochemical data are shown in Figure 6 and Table 2 [27] The difference here is due to Ttz tBu,Me being a weaker electron donor vs. Tp Me,Me . [30] Comparing to other (L)Cu II NO 2 complexes in the literature, our Cu II/I redox potential is much higher than the values for L 1 and L 2 complexes described in the introduction (E 1/2 = -0.027 V and -0.375 V vs. SCE with L 1 and L 2 , respectively) which makes sense because these ligands are stronger donors than Ttz tBu,Me .…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports illustrating the copper(I)-nitrito complexes could be a good model system for bio-relevant nitrite reduction despite their instability issue. [29][30][31] On the other hand, Cu(II)metal scaffolds (Scheme 1) such as the N 2 S ligand 24,25 and the hydrotris(triazolyl)borate ligand have been used for the reduction of nitrite to nitric oxide in the presence of an acid source using a cyclic voltametric reduction process. 31 Apart from them, triphenylphosphine (PPh 3 ) has also been used but under higher temperature conditions (60 °C) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The apparently rather simple active-site structure of CuNIR (a tripodal N-donor ligand which supports a copper centre undergoing a one-electron redox reaction) has led numerous groups of coordination chemists to attempt the synthesis of functional analogues of this enzyme [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most of these complexes bind only one molecule of nitrite, but Woollard-Shore et al [20] have reported two examples where two nitrite molecules are bound to a single Cu centre.…”
Section: Introductionmentioning
confidence: 99%